Local Excision ± Chemoradiotherapy vs. Total Mesorectal Excision for Early Rectal Cancer: Case-Matched Analysis of Long-Term Results - Pacevicius, Julius; Petrauskas, Vidas; Pilipavicius, Lukas; Dulskas, Audrius (Frontiers in Surgery, 2021)
BACKGROUND: our aim was to compare the bowel function and oncologic outcomes following local excision (LE) and total mesorectal excision (TME). MATERIALS AND METHODS: this was a single-center study with 67 patients included between 2009-2018. 32 were in TME group and 35 LE ± chemoradiation. We performed a case-matched analysis: we matched the patients by age, cancer stage, co-morbidities. Duration of operation, postoperative complications, length of hospital stay, long-term functional and oncologic outcomes were compared. We calculated oncologic outcomes using Kaplan-Meier Cox diagrams. In addition, we used low anterior resection syndrome (LARS) score for bowel function assessment. RESULTS: mean operation time in LE group was 58.8±45min compared to TME group – 121.1±42min (P=0.032). Complications were seen in 5.7% in LE and in TME group – 15.62% (P= 0.043). 85.2 % of patients had no LARS in LE group comparing to 54.5 % in TME group (p=0.018). Minor LARS 7.4% in LE group compared to 31.8 % in TME group (p=0.018); major LARS – 7.4 % and 13.7 % respectively (0.474). Hospital stay was 2.77 days in LE group compared to 9.21 in TME group (P=0.036). The overall survival was 68.78 months in LE group compared to 74.81 months in TME group (p=0.964). CONCLUSIONS: our results of a small sample size showed that local excision ± chemoradiation is rather safe method for early rectal cancer comparing with a gold standard treatment. In addition, better bowel function is preserved with less post-operative complications and shorter hospital stay.